2004
DOI: 10.1002/env.696
|View full text |Cite
|
Sign up to set email alerts
|

Modeling environmental data by functional principal component logistic regression

Abstract: SUMMARYIn recent years, many studies have dealt with predicting a response variable based on the information provided by a functional variable. When the response variable is binary, different problems arise, such as multicollinearity and high dimensionality, which prejudice the estimation of the model and the interpretation of its parameters. In this article we address these problems by using functional logistic regression and principal component analysis. In order to obtain a unique solution for the maximum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…A second possible expansion would be the functional data approach by considering the continuous-time character of the process and its sample-paths. Some previous research on this way has been done by Valderrama et al (2002), and Escabias et al (2005). 1 ARIMA (0,0,1) · (0,1,1) 6 223.8561 2 ARIMA (0,0,1) · (0,1,1) 6 24.9598 3 ARIMA (0,0,1) · (0,1,1) 6 -44.1591 …”
Section: Discussionmentioning
confidence: 97%
“…A second possible expansion would be the functional data approach by considering the continuous-time character of the process and its sample-paths. Some previous research on this way has been done by Valderrama et al (2002), and Escabias et al (2005). 1 ARIMA (0,0,1) · (0,1,1) 6 223.8561 2 ARIMA (0,0,1) · (0,1,1) 6 24.9598 3 ARIMA (0,0,1) · (0,1,1) 6 -44.1591 …”
Section: Discussionmentioning
confidence: 97%
“…The basis expansion of each observed curve x i (t) = p j=1 γ ij ψ j (t) can be estimated by an interpolation procedure (see Escabias et al (2005) for instance), if the curves are observed without noise, or by least square smoothing, if they are observed with error. In the present paper the second option will be used.…”
Section: Transformation Of the Observed Curvesmentioning
confidence: 99%
“…To overcome this problem, Ueki [19] As we know, functional regression models have been widely applied to engineering problems. For example, Escabias, Aguilera, and Valderrama [23] used functional logistic regression to deal with the environmental problem, which is to estimate the risk of drought in a specific zone from time evolution of temperatures. Sonja, Branimir, and DraDen [24] dealt with tool wear in milling process and the prediction of its behaviour by utilizing functional data analysis (FDA) methodology.…”
Section: Introductionmentioning
confidence: 99%